The urgency to reconstruction the law of concerning villages in obligations of village heads to resolve disputes and misdemeanors - Irwandi Ibrahim; Fenty U Puluhulawa; Dian Ekawati Ismail (The International Journal of Politics and Sociology Research, 2023)
The rural population is the basic capital of national development, which belongs to the people and nation of Indonesia. Villages have developed in various forms as part of the government structure and must be empowered to be strong, advanced and democratic so that they are able to carry out governance. In accordance with the mandate of the Law on Villages, the Village Head has the obligation to resolve disputes within the Village community. So far, the position of the village head in resolving conflicts is not clear, especially when minor crimes occur within the village community. This writing aims to examine how the urgency of the reconstruction of the Law on Villages in the obligation of the Village Head to Resolve Disputes and Misdemeanors. The research method used in the framework of this research is normative legal research method. The results of the study show that solving a problem that occurs in the village by placing the Village Head as a peace judge is a form of discretion/executive policy in order to realize public services for the community so that it is better to carry out a reconstruction of 26 paragraph (4) of Law No. 6 of 2014 concerning Villages.%MCEPASTEBIN%